HEPATOPROTECTIVE ACTIVITY OF BERBERISARISTATA ROOT EXTRACT AGAINST CHEMICAL INDUCED ACUTE HEPATOTOXICITY IN RATS - Dehar, Navdeep; Walia, Rani; Verma, R.B; Pandey, Pinky (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To study the effects of root extract of Berberis aristata in rat model of acute hepatotoxicity induced by carbon tetrachloride (CCl4). CCL4 is commonly used hepatotoxin in the experimental studies of liver diseases. Liver damage induced by CCL4 involves biotransformation of free radicals derivatives, increased lipid peroxidation and excessive cell death. Berberis aristata root extract, berberine chlorideâ€ is known to possess multiple pharmacological activities including anti-microbial, antiviral, anti-inflammatory, cholesterol lowering, anti cancer and anti-oxidant effects. The present study was conducted to evaluate the hepatoprotective activity of berberine in chemical induced hepatotoxicity in rats. Material & Methods: The experimental protocol was approved be the IAEC. Adult wistar rats aged 7-9 weeks were injected intraperitoneally with 50 percent CCl4 as 1:1 mixture in liquid paraffin. Berberine was administered i/p before or after CCl4 treatment in various groups. Twenty-four hours after CCl4 injection, serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase(ALP) activities, total serum bilirubin levels and liver weight were measured. Histological changes of liver were examined with microscopy. Results: Serum ALT, AST, ALP activities significantly decreased in a dose-dependent manner in both pre-treatment and post-treatment groups with berberine. Histological examination showed lowered liver damage in berberine-treated groups. Conclusion: The present study demonstrates that berberine possesses hepatoprotective effects against CCl4-induced hepatotoxicity and that the effects are both preventive and curative. Berberine should have potential for developing a new drug to treat liver toxicity. Â Key words: CCl4, Berberine, hepatoprotective activity, antioxidantÂ